2016
DOI: 10.1007/s00256-016-2339-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic osteoarthropathy with and without superimposed osteomyelitis in patients with a diabetic foot

Abstract: Soft tissue and bone infection involving the foot is one of the most common long-term complications of diabetes mellitus, implying a serious impairment in quality of life for patients in the advanced stages of the disease. Neuropathic osteoarthropathy often coexists and differentiating between these two entities is commonly challenging, but crucial, as the management may differ substantially. The importance of correct diagnosis cannot be understated and effective management requires a multidisciplinary approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 125 publications
0
31
0
1
Order By: Relevance
“…However, lower limb ischemia is a common diagnostic problem that also affects the correct interpretation of WBC scintigraphy, especially for the detection of STI, since a reduced vascular supply could impair leukocytes’ recruitment into infected sites [ 29 ]. Moreover, in the diabetic foot, the possible presence of Charcot and mechanical stress can be responsible for changes in the bone marrow or soft tissue intensity that could be erroneously interpreted as an OM, thus impairing the specificity of MRI [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, lower limb ischemia is a common diagnostic problem that also affects the correct interpretation of WBC scintigraphy, especially for the detection of STI, since a reduced vascular supply could impair leukocytes’ recruitment into infected sites [ 29 ]. Moreover, in the diabetic foot, the possible presence of Charcot and mechanical stress can be responsible for changes in the bone marrow or soft tissue intensity that could be erroneously interpreted as an OM, thus impairing the specificity of MRI [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Leone et al. (26) demonstrated that diffuse bone marrow involvement, ghost sign, replacement of soft tissue fat, sinus tract formation, progressive bony erosions, disappearance of subchondral cysts or intra-articular bodies, and diffuse joint fluid enhancement were more common in infected neuropathic osteoarthropathy than neuropathic osteoarthropathy without osteomyelitis, differentiation between them is challenging. To overcome these problems, we only included cases located on the forefoot, metatarsal head, calcaneus, and lateral malleolus, which are the most frequently involved anatomical sites of osteomyelitis in patients with diabetic foot (11,24).…”
Section: Discussionmentioning
confidence: 99%
“…Studies published in the last two decades have described the variable performance of 18 F-FDG PET in the assessment of DFI with a wide range of sensitivity and specificity [57,60]. Differences in patient populations, co-existing conditions such as hyperglycemia and peripheral artery diseases (PAD), and antibiotic usage make direct comparisons between multiple studies challenging [61,62]. While some preliminary studies suggest that hyperglycemia does not affect the diagnostic performance of 18 F-FDG, further validation is still required [63,64].…”
Section: Challenges In the Diagnosis And Treatment Of Dfismentioning
confidence: 99%